Communication and social learning: supporting local decision making on climate change, agriculture and food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Communication and social learning: supporting local decision making on climate change, agriculture and food security, Addis Ababa, Ethiopia From 8-10 May 2012